Social entrepreneurship - Rawls, Kevin, ....- (Iowa : Kendall Hunt Publishing, 2019)
Our society is looking for ways to bring together conscience and consumption. The rise of social entrepreneurship and social enterprises represents the growth of a business model that leverages market forces for sustained, positive, social impact. Social Entrepreneurship helps readers to understand that they can use their gifts and talents to make a change and make the world around them better. Written as a foundation for an upper-level course in social entrepreneurship (SE) or in a second-year course for business students, Social Entrepreneurship provides a general awareness of the issues that are influencing the state of SE in the US and globally.Kevin Rawls' Social Entrepreneurship: Is Contemporary! The publication contains updated information, such as those related to some of the current legal models. Is Student Friendly! Learning Objectives, Key Terms, Vignettes, and embedded references promote learning and comprehension. Promotes Application! Embedded case studies bring the content to life for readers.
Keywords: Sociaal ondernemen